Attendance of franchisee stakeholder’s interests and its relationship to financial performance in franchise networks - Ortega, Rubens Paulino; Melo, Pedro Lucas de Resende; Boaventura, João Maurício Gama; Mascena, Keysa Manuela Cunha de (Revista de Administração da UFSM, 2016)
The aim of this research was to analyze the relation between the attendance of the franchisee stakeholder and the financial performance of the franchise. It was proposed two research hypotheses by arguing that both the support as the brand may represent attendance of the interests of franchisees and have a positive relation with performance. Variables support and brand were obtained by publications of franchisees by the Brazilian Franchising Association (Official Guide to Franchising). The variable support considers the assessment of the franchisee regarding training, consulting and field operations manual and the variable brand refers to the perception of the franchisee on the brand strength, solidity and transparency. The multiple linear regression was used to test the hypotheses. The results did not confirm the hypothesis, since it was not found a significant relation between support and financial performance and found a negative relationship between brand and financial performance in the analyzed sample. Although it was found negative relation, it does not weaken the use of stakeholder theory in the study of franchises, given the current literature proposition that, instead of giving priority service to a more relevant stakeholder, should consider the potential of creation value in the relationship with several stakeholder groups simultaneously.